How do Patients Receiving Antiretroviral Therapy (ART) at A Dedicated ART Center in Bhagalpur Demonstrate Observable Patterns and Outcomes in an Observational Study? - Choudhary, Raj Kamal; Singh, Amrendra Kumar; Ojha, Shubham; Verma, Vinay Kumar; Kumar, Avinash; Bhagat, Ravi Kishan; Gupta, N K; Kumar, Abhilesh; Pervez, Anjum; Fatima, Sidratil (South Eastern European Journal of Public Health, 2024)
Ours study provides a comprehensive overview of the HIV/AIDS landscape in Bhagalpur, Bihar, focusing on patients receiving Antiretroviral Therapy (ART). Conducted over six years, involving 10,355 participants, the research explores demographic details, treatment outcomes, and treatment-seeking behaviors. Notably, 100% participation reflects the community's engagement, with detailed analyses of gender-specific registrations, treatment initiation, and outcomes. The study delves into patients' geographic origins, travel distances, and factors influencing their preferences. Insightful discussions on perceptions regarding HIV and ART underscore societal challenges. Positive aspects include family support and awareness, yet concerns like substance use and travel barriers need attention. The study concludes with recommendations for targeted interventions to enhance HIV/AIDS care effectiveness. Limitations highlight the need for broader community comparisons, emphasizing the study's contribution to shaping future research and healthcare strategies. The acknowledgment expresses gratitude for mentorship and collaborative efforts in completing the project.